2019
DOI: 10.3389/fnins.2019.00420
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Differences in Speech Processing Among Older Hearing-Impaired Listeners With or Without Hearing Aid Experience: Eye-Tracking and fMRI Measurements

Abstract: Recently, evidence has been accumulating that untreated hearing loss can lead to neurophysiological changes that affect speech processing abilities in noise. To shed more light on how aiding may impact these effects, this study explored the influence of hearing aid (HA) experience on the cognitive processes underlying speech comprehension. Eye-tracking and functional magnetic resonance imaging (fMRI) measurements were carried out with acoustic sentence-in-noise (SiN) stimuli complemented by pairs of pictures t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 45 publications
0
10
2
Order By: Relevance
“…Using fMRI measures, they found decreased activity-compared to a baseline measure before hearing aid fitting-in the superior temporal gyrus following the presentation of speech sounds to the unaided ear as well as the aided ear. Finally, Habicht et al 28 used fMRI measures and found decreased activity in superior and middle frontal regions outside of the speech processing network in hearing aid users compared to hard-of-hearing unaided listeners when processing speech in noise. In addition, they found increased activity in the lingual gyri and the left precuneus with longer hearing aid use when processing complex sentences.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Using fMRI measures, they found decreased activity-compared to a baseline measure before hearing aid fitting-in the superior temporal gyrus following the presentation of speech sounds to the unaided ear as well as the aided ear. Finally, Habicht et al 28 used fMRI measures and found decreased activity in superior and middle frontal regions outside of the speech processing network in hearing aid users compared to hard-of-hearing unaided listeners when processing speech in noise. In addition, they found increased activity in the lingual gyri and the left precuneus with longer hearing aid use when processing complex sentences.…”
mentioning
confidence: 99%
“…In addition, they found increased activity in the lingual gyri and the left precuneus with longer hearing aid use when processing complex sentences. Since decreased activity in frontal regions has been found when hearing aid use was used as a grouping factor 27,28 , but increased activity in other regions has been found to correlate with length of hearing aid use 28 , both the location and the direction of the influence of hearing aid use on neural processing remain unclear. In addition, many of these studies had small sample sizes (e.g., groups of 8 27 or 13 28 participants) and in Habicht et al 28 the significance thresholds were not corrected for multiple comparisons.…”
mentioning
confidence: 99%
See 3 more Smart Citations